Feasibility study on energy prediction of microwave ablation upon uterine adenomyosis and leiomyomas by MRI - Xia, M (The British Institute of Radiology., 2014)
OBJECTIVE: To evaluate the feasibility of energy prediction of percutaneous microwave ablation (PMWA) upon uterine leiomyomas and adenomyosis by MRI. METHODS: 63 patients (49 patients with 49 uterine leiomyomas and 14 patients with adenomyosis) who underwent ultrasound-guided PMWA treatment were studied during the period from June 2011 to December 2012. Before PMWA, contrast-enhanced MRI (ceMRI) was performed for all of the patients. Based on the signal intensity (SI) of T(2) weighted MRI, uterine leiomyomas were classified as hypointense, isointense and hyperintense. During ablation, the output energy of the microwave was set at 50 W, and T11a microwave antennas were used. ceMRI was performed within 7 days after PMWA treatment. Non-perfused volume and energy required per unit volume were analysed statistically. RESULTS: When unit volume of lesions was ablated, uterine adenomyosis needed more energy than did uterine leiomyomas, and hyperintense uterine leiomyomas needed more energy than did hypointense pattern. CONCLUSIONS: MRI SI of uterine leiomyomas and uterine adenomyosis can be used to predict PMWA energy. ADVANCES IN KNOWLEDGE: The conclusions indicate that MRI SI can be used to perform pre-treatment planning, which will make the treatment more precise.